The role of estrogen receptor β in maintaining basal cells and modulating the immune environment in the prostate - Wan-fu Wu; Xiao-Yu Song; Margaret Warner; Otabeck Imamov; Per Antonson; Jan-Ake Gustafsson (Proceedings of the National Academy of Sciences, 2025)
Estrogen receptor β (ERβ) plays an important role in both the mouse and human prostate. The endogenous ligand for ERβ is the dihydrotestosterone metabolite, 5β-androstane-3β, 17β-diol (3β-Adiol). Thus, treatment with 5-α reductase inhibitor (5-ARI) should produce a phenotype similar to that seen in ERβ −/− mice. By comparing RNA-Seq of the ventral prostates (VP) of ERβ knockout mice (ERβ crispr−/− ) and wild-type (WT) mice, we confirmed that ERβ modulates androgen receptor (AR) signaling indirectly by suppressing AR coactivators. Compared to WT mice, basal cell genes from ERβ crispr−/− mouse VP were significantly upregulated. A population of abnormal basal cells coexpressing P63 and AR was identified in the ERβ crispr−/− mouse VP by immunohistochemistry. In men treated with 5-ARI for treatment of benign prostatic hyperplasia (BPH), there was induction of a P63-positive intermediate cell population characterized by down regulation of Krt14 without significant change in the expression of Krt15, upregulation of AR and NKX3.1, and increased proliferation. In both VP of aging ERβ crispr−/− mice and in human prostates after 5-ARI treatment, there was substantial immune infiltration. Testosterone treatment inhibited immune infiltration in the VP of ERβ crispr−/− mice. We conclude that ERβ is a gene critical in maintaining normal basal cells and modulating immune environment in the prostate. Its loss leads to histological changes suggesting prostatitis and increases the number of intermediate cells, which are considered to be the cells of origin of prostate cancers. We suggest that an ERβ agonist could protect against 5-ARI-induced inflammatory cell infiltration and defects in the basal cell layer in BPH.